Decomposition of the Gini index in the presence of observations with negative values - Ostasiewicz, Katarzyna; Vernizzi, Achille (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
The problem of calculating the Gini index in the presence of negative inputs may be overcome by decomposing the quantity at stake into “positive” and “negative” parts, which, by definition, include only non-negative values. For such constructed sources, concentration indexes may be calculated and their influence on the overall inequality evaluated. In the paper we present the methodology of such an assessment and illustrate it with the example of Italian income data
Mathematical Economics, 2018, Nr 14 (21), s. 37-50
Keywords: inequality; Gini index; negative inputs; decomposition